2015
DOI: 10.1515/pjs-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumoperitoneum in a Patient After Ventilation Therapy

Abstract: Free gas in the peritoneal cavity is not always associated with gastrointestinal perforation. The study presented a case of a 72-year old male patient with peritoneal emphysema, which developed after ventilation therapy. Suspecting gastrointestinal perforation the patient was subjected to laparotomy, which did not show perforation. The patient was diagnosed with spontaneous pneumoperitoneum. The patient died, due to cardiopulmonary and neurological disturbances. Withdrawal from non-therapeutic laparotomy may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Gantt et al [ 3 ] suggested that the origin of SP indicated intra-thoracic, intra-abdominal, gynecological, and iatrogenic causes. The intra-thoracic causes include barotrauma pneumothorax [ 4 ], bronchoperitoneal fistula [ 5 ], pneumomediastinum [ 6 ], and mechanical ventilation [ 7 ]. The intra-abdominal causes include abdominal emphysematous cholecystitis [ 8 ], spontaneous bacterial peritonitis [ 9 ], intestinal cystic pneumatosis [ 10 , 11 , 12 , 13 , 14 , 15 ], and liver abscess [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gantt et al [ 3 ] suggested that the origin of SP indicated intra-thoracic, intra-abdominal, gynecological, and iatrogenic causes. The intra-thoracic causes include barotrauma pneumothorax [ 4 ], bronchoperitoneal fistula [ 5 ], pneumomediastinum [ 6 ], and mechanical ventilation [ 7 ]. The intra-abdominal causes include abdominal emphysematous cholecystitis [ 8 ], spontaneous bacterial peritonitis [ 9 ], intestinal cystic pneumatosis [ 10 , 11 , 12 , 13 , 14 , 15 ], and liver abscess [ 16 ].…”
Section: Discussionmentioning
confidence: 99%